COMPARATIVE CLINICAL STUDY OF NARIKEL TAIL SHIROBHYANGAM AND PADABHYANGAM UPAKRAMA ON NIDRANASH - Zambare Smita Vinod (International Journal of Applied Ayurved Research, 2017)
Ayurveda is a science of life. Sleep is one of the important piller for healthy life. nidranash (sleeplessness) has become a very common life style disorder to human being, resulting in various problems such as stress, disturbed sleep, mental illness etc. The most convenient & easiest way, according to Ayurveda, to overcome “Nidranash” is “Shirobhyangam” (head massage) and “Padabhyangam” (foot massage). Narikel tail has been used as massage oil because of its guru, snigdha, bruhana, sheeta veerya properties. It has good odour ,affordable price ,easily available. Benefits associated with narikel tail massage have been attributed for sound sleep by shirobhyangam & padabhyangam. Clinical comparative trials on group “A” for “Shirobhyangam” and on group “B” for “Padabhyangam” was done to determine the efficacy of narikel tail in Dinacharya upakrama for sound sleep.